Mental health conditions and adherence to direct oral anticoagulants in patients with incident atrial fibrillation: A nationwide cohort study - Teppo Konsta; Jaakkola Jussi; Airaksinen K. E. Juhani; Biancari Fausto; Halminen Olli; Putaala Jukka; Mustonen Pirjo; Haukka Jari; Hartikainen Juha; Luojus Alex; Niemi Mikko; Linna Miika; et al. (ELSEVIER SCIENCE INC, 2022)
Objective: Medication adherence is essential for effective stroke prevention in patients with atrial fibrillation (AF). We aimed to assess whether adherence to direct oral anticoagulants (DOACs) in AF patients is affected by the presence of mental health conditions (MHCs).
Methods: The nationwide FinACAF cohort covered 74,222 AF patients from all levels of care receiving DOACs during 2011-2018 in Finland. Medication possession ratio (MPR) was used to quantify adherence. Patients with MPR >= 0.90 were defined adherent. MHCs of interest were depression, bipolar disorder, anxiety disorder and schizophrenia.
Results: The patients' (mean age 75.4 +/- 9.5 years, 50.8% female) mean MPR was 0.84 (SD 0.22), and 59.5% had MPR >= 0.90. Compared to patients without MHC, the adjusted ORs (95% CI) for adherent DOAC use emerged slightly lower in patients with depression (0.92 (0.84-0.99)) and bipolar disorder (0.77 (0.61-0.97)) and unsignificant in patients with anxiety disorder (1.08 (0.96-1.21)) and schizophrenia (1.13 (0.90-1.43)). However, when only persistent DOAC therapy was analyzed, no MHC was associated with poor adherence, and instead anxiety disorder was associated with adherent DOAC use (1.18 (1.04-1.34)).
Conclusion: Adherence to DOACs in AF patients in Finland was relatively high, and no meaningful differences between patients with and without MHCs were observed.